Ecosystem-based adaptation - Uy, Noralene; Shaw, Rajib (Emerald, 2012)
Ecosystems are often examined from an ecological perspective because of the importance of biodiversity and ecosystem services. Ecosystems of different types and scales are under increasing pressure due to natural and human induced changes. Climate change and the disasters it causes, are a major driver affecting ecosystems and services. Several studies have provided evidence that a healthy ecosystem helps in reducing the impacts of climate change and disasters. This book makes a case for ecosystem-based adaptation by arguing that ecosystems and its services are critical in the climate change and disaster risk reduction fields. Consequently, the monitoring and regulation of ecosystems need to be linked to a regular governance and institutional mechanism and be reflected in a more action-oriented agenda.
Keywords: Ecosystem management.; Climatic changes -- Environmental aspects.; Ecological disturbances -- Prevention.; elektronické knihy; electronic books